THE CITY AND URBAN NETWORKS RE-STRUCTURING NEXUS: THE SPACIAL IMPLICATIONS OF THE INSTALLATION OF THE BELO MONTE MINE IN ALTAMIRA-PA AND ITS REGION OF INFLUENCE - Miranda Neto, Jose Queiroz de [UNESP] (Univ Estadual Paulista Julio Mesquita Filho, 2017)
This article deals with the role of the hydroelectric power plant of Belo Monte in the spatial transformations in Altamira-PA and its region of influence (RIA). For purposes of analysis, the city of Altamira is considered a medium-sized cit, allowing us to use the authors, the theoretical approaches and the variables used to deal with this theme in Brazil. During the research, it was understood that formulations so far developed regarding medium-sized cities, while being relevant, need further explanation to reach a coherent formulation regarding the reality under study. From a theoretical perspective that articulates the concepts of structure, structuring and its relations with the social space, comes a formulation denominated nexuses of re-structuring of the city and the urban network, that designates a necessary methodological form to read the reality of Altamira and its region of influence in its movement, with layers and nuances necessary to discern the new and the old in the process of transformation.
Keywords: Reestructuring the city; Urban restructuring; Altamira; Brazilian Amazon